Inhibition of polycomb repressor complex 2 ameliorates neointimal hyperplasia by suppressing trimethylation of H3K27 in vascular smooth muscle cells. (19th July 2019) - Liang, Jing; Li, Qi; Cai, Wenbin; Zhang, Xuejiao; Yang, Bing; Li, Xin; Jiang, Shuai; Tian, Shanshan; Zhang, Kai; Song, Hao; Ai, Ding; Zhang, Xu; et al.
Abstract : Background and Purpose: The increased proliferation and migration of vascular smooth muscle cells (VSMCs) after arterial injury contributes greatly to the pathogenesis of neointimal hyperplasia. As a major component of epigenetics, histone methylation plays an important role in several cardiovascular diseases. However, its role in restenosis is still unclear. Experimental Approach: Human aortic VSMCs were challenged with PDGF‐BB, and total histones were extracted and analysed by HPLC/MS. For the in vivo study, rats were subjected to wire‐guided common carotid injury. Key Results: PDGF‐BB markedly increased the H3K27me3 level, as demonstrated by use of HPLC/MS and confirmed by western blot analysis. Enhancer of zeste homologue 2 (EZH2), the histone H3K27 methyltransferase component of polycomb repressive complex 2, was also up‐regulated by PDGF‐BB in VSMCs, and in the neointimal hyperplasia induced by wire injury of the rat carotid artery. Furthermore, inhibiting H3K27me3 by treatment with 3‐μM UNC1999, an EZH2/1 inhibitor, significantly suppressedPDGF‐BB ‐induced VSMC proliferation compared with thePDGF‐BB ‐treated group. Consistently, neointimal formation was significantly attenuated by oral or perivascular administration of UNC1999 compared with the sham group. Mechanistically, the increase in H3K27me3 inhibited the transcription of the cyclin‐dependent kinase inhibitor p16 INK4A and thus promoted VSMC proliferation. Conclusions and Implications: Vascular injury elevated the expression of EZH2 and the downstream target H3K27me3, which suppressed p16 INK4A expression in VSMCs and promoted VSMC proliferation and neointimal hyperplasia. EZH2 inhibition might be a potential therapeutic target for restenosis.